An experiment on the layout and grounding of power distribution wires in a printed circuit board - Chung, BK (2001)
An experiment has been designed with the aim to enhance the students' understanding in the topic of conducted electromagnetic interference (EMI). A printed circuit board (PCB) is developed with a motor driver circuit, a digital clock generator, and a sinewave oscillator on board. The digital and analog signals are monitored using an oscilloscope to study the interference effects. The circuit module is duplicated with a different grounding system. A separate ground system proves to be very effective in reducing the conducted EMI. Further noise reduction can be achieved using decoupling capacitors or L-network filters. The effectiveness depends on the location where these additional components are applied. The effect of ground loop is also studied in the experiment.